Gate-tuned graphene meta-devices for dynamically controlling terahertz wavefronts - Li Qiushi; Cai Xiaodong; Liu Tong; Jia Min; Wu Qiong; Zhou Haoyang; Liu Huanhuan; Wang Qianqian; Ling Xiaohui; Chen Cong; Ding Fan; He Qiong; et al. (Nanophotonics, 2022)
Dynamical controls on terahertz (THz) wavefronts are crucial for many applications, but available mechanism requests tunable elements with sub-micrometer sizes that are difficult to find in the THz regime. Here, different from the local-tuning mechanism, we propose an alternative approach to construct wavefront-control meta-devices combining specifically designed metasurfaces and globally tuned graphene layers. Coupled-mode-theory (CMT) analyses reveal that graphene serves as a tunable loss to drive the whole meta-device to transit from one functional phase to another passing through an intermediate regime, exhibiting distinct far-field (FF) reflection wavefronts. As a proof of concept, we design/fabricate a graphene meta-device and experimentally demonstrate that it can reflect normally incident THz wave to pre-designed directions with different polarizations under appropriate gating voltages. We finally design a graphene meta-device and numerically demonstrate that it can generate vectorial THz beams with continuously varying polarization distributions upon gating. These findings pave the road to realizing a wide range of THz applications, such as sensing, imaging, and wireless communications.